Pola Komunikasi Petugas Lembaga Pemasyarakatan Dalam Pembinaan Warga Binaan Di Lapas Kelas II B Kabupaten Empat Lawang - Rahma , Nurul Aulia; Hamidah, Hamidah; Yahya, Ahmad Harun (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This thesis is entitled "Communication Patterns of Correctional Institution Officers in the Development of Inmates in Class II B Prisons, Empat Lawang Regency". The aim of the first research was to determine the communication of correctional institution officers in coaching inmates, in class II B prisons in the district. Four gates. Second, factors that support communication between officers and inmates in class II B prisons. Third, to find out the obstacles experienced by correctional officers in communication patterns with inmates who experience cognitive dissonance in class II B prisons in the district. Four Lawangs. The research uses qualitative methods. Data collection techniques through observation, interviews and documentation. The results of the research show that first, a coach must have a positive attitude, so that he can encourage his coachees to participate in creating effective interpersonal communication. A coach will always give a positive feeling or a positive attitude to the coachees because of that positive feeling by carrying out activities that inmates can do this while they are still outside prison or before becoming prisoners. Second, there is full support from the leadership institution's program and coaching loyalty so that the more integrated the system for implementing positive activities is, the more opportunities it provides for the target residents to achieve better personal change. Third, the obstacle is that there are still inmates who have unfavorable attitudes towards correctional institution employees.